Synthesis and Photocatalytic Activity of Fe-doped TiO2 Supported on Hollow Glass Microbeads - Zhao, Wenyan; Fu, Wuyou; Yang, Haibin; Tian, Chuanjin; Li, Minghui; Ding, Juan; Zhang, Wei; Zhou, Xiaoming; Zhao, Hui; Li, Yixing (Nano-Micro Letters, 2011)
In this paper, Fe-doped TiO2 photocatalyst supported on hollow glass microbeads (Fe-TiO2/beads) is prepared by dip-coating method, which uses hollow glass microbeads as the carriers and tetrabutylorthotitanate [Ti(OC4H9)4] as the raw material. The phase structure, ingredient, morphologies, particle size and shell thickness of the products are characterized by X-ray powder diffraction (XRD), energy-dispersive spectroscopy (EDS) and field emission scanning electron microscope (FESEM). The feasibility of photocatylic degradation of Rhodamine B (RhB) under illumination of UV-vis light is studied. The results show that the core-shell structure catalyst is composed of Fe-doped anatase TiO2 and hollow glass microbeads, and the catalytic activity of the TiO2 is markedly enhanced by Fe ion doping. The optimum concentration of Fe ion is 0.1% (molecular fraction) in the precursor and the photocatalytic activity can be increased to 98% compared with that of the undoped one. The presence of ferrum elements neither influences the transformation of anatase to rutile, nor creates new crystal phases. The possible mechanism of photocatalytic oxidation is also discussed.